Social Facilitation Revisited: Increase in Foraging Efforts and Synchronization of Running in Domestic Chicks - Ogura, Yukiko; Matsushima, Toshiya (Frontiers in Neuroscience, 2011)
Social influences on foraging efforts were examined in domestic chicks by investigating the frequency of runs made to feeders and the amount of pecking to gain food. Single or paired chicks foraged in an I-shaped maze equipped with a millet feeder on each end, that distributed one or two grains at variable intervals. Regardless of when the grain(s) were dispensed, chicks ran back and forth between the feeders. Analyses of their movement patterns revealed: (1) running patterns were not directly synchronized with the dispensing of grain(s), (2) running distance was longer in paired chicks than in single chicks, (3) paired chicks partially synchronized their runs between feeders, and (4) social effects were immediate but cumulative after repeated blocks. We further examined the social effects on running by dividing the I-maze into two parallel lanes separated by a transparent wall, so that kleptoparasitic interference of food did not occur. Again, the chicks increased their running speed and were even more synchronized with their partner’s movements, indicating that food competition alone was not responsible for increased foraging effort. The number of pecks to get grains was also assessed under conditions where the food tray was gradually replaced, from an easy one to more difficult ones. When tested in the separated I-maze, paired chicks pecked more in the difficult food situation without increase in the number of gained grains. Results suggest that (i) social facilitation leads to increased foraging efforts and (ii) the presence of a conspecific is alone may lead to enhanced foraging efforts in chicks. These findings are discussed in terms of possible ecological background of social facilitation.